Global analysis of alternative splicing in human cells of myeloid origin - Lorenzini Paolo Alberto (2018)
Pre-mRNA splicing is one of the processing steps by which the genetic information flows in a biological system for functional gene expression. Alternative splicing plays an important role in the development of eukaryotic cells during which the activity of the splicing regulatory machinery changes dynamically. Perturbations in alternative splicing are at the basis of a wide spectrum of human diseases. Recent investigations have shown that alternative splicing plays a role in the homeostasis of lymphoid cells in order to mount an efficient adaptive immune response. However, a detailed characterization of the role of alternative splicing in myeloid cells during an innate immune response is lacking. The characterization of alternative splicing events in myeloid cells will provide a basis to study perturbations that occur in various human disorders such as allergies, autoimmune diseases and cancers. Thus, we performed two transcriptome studies by RNA-sequencing in the aforementioned cells. In the first study, we performed analysis of the human monocytes and various subtypes of macrophages derived from them, both in the THP-1 cell line and in primary human cells. We identified genes that changed mRNA expression and changes in alternative splicing during the differentiation from monocytes to macrophages and during their polarization to various macrophage subsets. We found that alternative splicing plays a major role in the differentiation process and in the polarization of M1 macrophages but likely less in the activation of the M2 macrophages to the various subsets. In the second study, we successfully knocked out by CRISPR the splicing factor PRPF40B in K562 cell line. We rescued the knock out cells by overexpressing PRPF40B as wild-type or as mutated by introducing in the wild-type gene two mutations of the factor found in myelodysplastic syndromes. We found that PRPF40B controls the alternative splicing of thousands of events, hundreds of which are cassette exons, mainly repressing their inclusion, and we proved that it occurs co-transcriptionally. In addition, we found an activation of a hypoxia gene signature in the KO cells thus showing that PRPF40B has a role in inhibiting hypoxia, in contrast to its homologue PRPF40A which instead promotes it. We found that when PRPF40B is mutated, no major changes in gene expression and alternative splicing are occurring thus showing that the two mutations might be just passengers. Unexpectedly, we found a possible contrasting role of PRPF40A and PRPF40B in regulating hypoxia in Acute Myeloid Leukemia which could lead to a potential therapeutic application to decrease chemoresistance.